Political Mediatization in Memes: A Netnography Study on Ganjar Pranowo & Mahfud MD Candidate Memes for The 2024 Period - Alfa Pandutama; Almira Kusumowardani Habsari; Azizah Laurensia Achmad; Muhammad Alviansyah Hidayat (Eduvest - Journal of Universal Studies, 2024)
Memes as digital content with humorous characteristics are an important part of online interaction on social media. The existence of memes in politics acts as a rhetorical tool and discursive argument, with its use to convey messages with political content. The use of memes as political mediatization in the 2019 elections in Indonesia as an expressive form of the success team of the Presidential and Vice Presidential candidates at that time. This study examines political mediatization through memes that occurred in the candidates Ganjar Pranowo and Mahfud MD in the 2024 Indonesian President and Vice President elections. Using a netnographic method, the research identifies five categories of meme usage- pure humor, ridicule, general political information, candidate information, and expressions of support.. These memes, originally light-hearted, evolved into strategic tools shaping a relaxed and approachable political image. This study highlights how media logic has transitioned into social media logic, prioritizing personalized content and user engagement to influence public perception. This transition underscores the effectiveness of memes in altering political narratives and fostering voter interaction during campaigns.